Transparansi Pengelolaan Anggaran Daerah Di Satuan Kerja Perangkat Daerah (SKPD) Kabupaten Bulukumba Tahun 2014 - Latief, Firmanto; Mutiarin, Dyah (Universitas Muhammadiyah Yogyakarta, 2016)
The problems discussed in this study is the transparency of budget management in the area work unit (SKPD)Bulukumba Lodging at the Department of Education, Youth and Sports Bulukumba, Department of Health, Office ofFinancial Management and the Department of Highways. This study aims to determine the performance oftransparency in the management of local budgets in the regional work units Bulukumba and factors that affect theapplication of transparency. The method used in this penelitiian is the combination of qualitative and quantitativemethods, sample in this study of 60 people with menggunanakan purposive sampling method. There are two typesof data analysis applied in this study, the analysis of qualitative and quantitative analysis. The results showed thatthe transparency of budget management conducted by the Department of Education, Youth and Sports Bulukumbaof several indicators has a value of cumulative index 2:02 by category Less Good, transparency of budgetmanagement conducted by the Office of Financial Management Bulukumba of several indicators has a value ofcumulative index 2. 81 with good category, transparency of budget management is conducted by the Department ofHealth Bulukumba of several indicators has a cumulative index score of 1. 98 with the category of Less Good,transparency of budget management is carried out by the Highways Agency Bulukumba of several indicators has acumulative index score 2:09 with Less Good category.